Indicators for the Sea-floor Integrity of the Hellenic Seas under the European Marine Strategy Framework Directive: establishing the thresholds and standards for Good Environmental Status - SIMBOURA, N.; ZENETOS, A.; PANCUCCI-PAPADOPOULOU, M.A.; REIZOPOULOU, S.; STREFTARIS, N. (Mediterranean Marine Science, 2012)
A data set of 625 samples of benthic macroinvertebrates collected from the Hellenic Seas (Ionian and Aegean) was used to establish thresholds and reference standards for two of the indicators addressing the descriptors of Sea-floor Integrity under the Marine Strategy Framework Directive (MSFD): species diversity and richness and the ratio of sensitive species to tolerant species. The dataset was categorised according to the baseline ecological status assessment of the respective water bodies under the Water Framework Directive (WFD). Species diversity and richness were characterised using the Shannon diversity and species richness indices, respectively, and were analysed for three pre-defined substrate types, three depth zones and three sample-size categories, and the significant categories were statistically validated. Good Environmental Status (GEnS) threshold and reference values were established for the valid combinations of categories denoted as ‘ecotypes’ through the use of a boxplot and an analysis of variance. The limitations and specifications for an overall GEnS assessment using the above indices are highlighted based on the WFD experience. For the ratio of sensitive species to tolerant species, the BENTIX index classification scale is proposed for GEnS assessment, and an integrated approach to the assessment of diversity and species richness is suggested. Finally, the regionality of the tested indices in relation to the two Mediterranean sub-regions, including the Hellenic area, was tested.